Phylogenetic and epidemiological insights into centenarians’ resilience to COVID-19: exploring the role of past coronavirus pandemics - Romano, Greta; Ferrari, Alessandro; Baldanti, Fausto (Frontiers in Microbiology, 2025)
In the 20th and 21st centuries, humanity has faced several global crises, including world wars, the 1918 Spanish flu, and the recent COVID-19 pandemic. Notably, the COVID-19 pandemic caused significant mortality, particularly among older adults, while younger ages were less affected. Strikingly, according to the Italian National Institute of Statistics (Istat), centenarians (aged 100 and above) in Italy experienced no significant increase in mortality in 2020. This retrospective study hypothesizes that elderly people may have developed an immune response that offered protection against COVID-19, potentially linked to their exposure to a specific past infectious event. We examined historical mortality data from 1872 to 2021 and performed phylogenetics analysis on sequencing data to explore the possibility that centenarians may have encountered another Coronavirus (misidentified as Russian Flu), which could have contributed to their resilience. This research provides insights into the adaptive responses of the most vulnerable populations, symbolically comparing them to the “left-standing trees” following catastrophic events.